2010
DOI: 10.1111/j.1540-4560.2010.01661.x
|View full text |Cite
|
Sign up to set email alerts
|

Group Devaluation and Group Identification

Abstract: In three studies, we showed that increased in-group identification after (perceived or actual) group devaluation is an assertion of a (preexisting) positive social identity that counters the negative social identity implied in societal devaluation. Two studies with real-world groups used order manipulations to show that the (perceived or actual) devaluation of an in-group led individuals to increase their identification with this in-group. Group devaluation most strongly and consistently increased individuals'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 21 publications
(50 reference statements)
5
84
0
1
Order By: Relevance
“…Identification with various types of groups can be conceptualized by a dimension that captures the extent to which individuals perceive themselves and other in-group members as a category (i.e., self-definition), and a dimension that captures the extent to which individuals' are psychologically invested in the ingroup (i.e., self-investment). Moreover, the differential influence of the group on individuals' self-definition and self-investment provides further evidence of the validity of the distinction between these two dimensions of identification (see also Leach, Rodriguez Mosquera, Vliek, & Hirt, 2010;Shepherd, Spears, & Manstead, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Identification with various types of groups can be conceptualized by a dimension that captures the extent to which individuals perceive themselves and other in-group members as a category (i.e., self-definition), and a dimension that captures the extent to which individuals' are psychologically invested in the ingroup (i.e., self-investment). Moreover, the differential influence of the group on individuals' self-definition and self-investment provides further evidence of the validity of the distinction between these two dimensions of identification (see also Leach, Rodriguez Mosquera, Vliek, & Hirt, 2010;Shepherd, Spears, & Manstead, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…MPlus (Muthén & Muthén, 1998-2010 was used to perform a multigroup (between-studies) multilevel confirmatory factor analysis (CFA) that specified the two-dimensional model of in-group identification at both the individual (Level 1) and the group level (Level 2). In the model, the individual self-stereotyping and in-group homogeneity components loaded on a self-definition factor, and the solidarity and satisfaction components loaded on a self-investment factor.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals draw closer to their group when they encounter prejudice or discrimination (Branscombe et al, 1999;Jetten, Branscombe, Schmitt, & Spears, 2001;Knowles & Gardner, 2008), and this has been shown to protect self-esteem (Bourguignon, Seron, Yzerbyt, & Herman, 2006), prevent depression (Sani, Herrara, Wakefield, Boroch, & Gulyas, 2012), and reduce destructive behavior in response to exclusion (Stock, Gibbonds, Walsh, & Gerrard, 2011). Importantly, individuals only increase group identification after encountering prejudice if they are already highly identified with their group (McCoy & Major, 2003;Wann & Branscombe, 1990), clarifying that identification is better seen as a resource than as a coping strategy (Leach, Rodriguez Mosquera, Vliek, & Hirt, 2010). Recent knowledge regarding some of the mechanisms underlying this protective effect clarifies that group identification promotes social support seeking (Haslam, O'Brien, Jetten, Vormedal, & Penna, 2005) and exposure to a positive definition of the group from the "inside," which helps combat more external negative views (Crabtree, Haslam, Postmes, & Haslam, 2010).…”
Section: The Role Of Group Identificationmentioning
confidence: 90%
“…Research stemming from the social identity theory has comprehensively shown that ethnic identity becomes salient for minority members when interacting with the majority group (Smith & Leach, 2004;Waters, 1990). Therefore, the strong ethnic identity among Slovenes may reflect a tendency to stress their distinctiveness from the majority outgroup, and to maintain a clear sense of self within an inclusive group of moderate size and a positive self-view (Branscombe, Schmitt, & Harvey, 1999;Leonardelli & Brewer, 2001;Pickett & Leonardelli, 2006), as well as being a counter-reaction to perceived marginalization, discrimination and hostility (Leach, Rodriguez Mosquera, Vliek, & Hirt, 2010;Verkuyten & Nekuee, 1999). Interestingly, the Slovene ethnic identity did not contribute to well-being as much as the Italian national identity.…”
Section: Discussionmentioning
confidence: 89%